Role of Glutamatergic System in Obsessive-Compulsive Disorder with Possible Therapeutic Implications - Vlček, Přemysl; Polák, Jakub; Brunovský, Martin; Horáček, Jiří (Pharmacopsychiatry, 2018)
Obsessive-compulsive disorder (OCD) is a chronic psychiatric illness and 1 of the most common anxiety disorders with the prevalence of 3%. Although its pathogenesis remains unclear, the traditional model focused on alternations in the serotonin system. Selective serotonin reuptake inhibitors provide the most effective treatment; however, as much as 40-60% of patients do not respond to antidepressants therapy. Thus, attention has shifted towards other neurotransmitter systems and related neuroanatomical structures. Recently, there is extensive evidence showing a key role of glutamate pathways abnormalities within the cortico-striatal-thalamo-cortical circuitry and temporal lobes in OCD pathogenesis. In this review, we link together the existent neuroanatomical, neurophysiological, and neuropsychological evidence to argue for potential benefits of adjuvant treatment with glutamatergic agents, especially memantine. By a targeted de-excitation effect on the glutamatergic system in the temporal lobes and connected brain regions, memantine might further alleviate OCD symptoms. This effect should be even more pronounced in certain subtypes of patients with specific cognitive deficits and maladaptive compensatory memory processes (e.g., checkers).
Keywords: Female; Brain; kognitivní poruchy; Cognition Disorders; Glutamic Acid; mužské pohlaví; Humans; glutamátové receptory; Receptors, Glutamate; Excitatory Amino Acid Agents; lidé; kyselina glutamová; obsedantně kompulzivní porucha; mozek; neuropsychologické testy; látky působící na systém excitačních aminokyselin; ženské pohlaví; Neuropsychological Tests; Obsessive-Compulsive Disorder; Male